E rosetting lymphocytes in inflammatory bowel disease. An analysis using monoclonal antibodies. - Makiyama, K; Selby, W; Jewell, D (1983)
Lymphocytes rosetting with sheep red blood cells (SRBC) have been quantitated in the peripheral blood of patients with ulcerative colitis (UC) or Crohn's disease (CD) and the results compared with those from healthy control subjects. In contrast with previous studies, normal populations of total (SRBC: lymphocyte, 60:1) and avid (8:1) rosetting lymphocytes were found in the patient groups. Analysis of these cells, using monoclonal antibodies, showed that the proportions of OKT3+, OKT4+ and OKT8+ cells were similar in the two rosetting populations. However, for patients with UC, there was a significant increase in OKT4+ cells in the total rosette forming population when compared with healthy subjects. It is concluded that avid rosette forming cells are unlikely to form a functionally distinct population of T lymphocytes and this population, which is thymosin-dependent, is not deficient in patients with UC or CD.